Pemanfaatan Teknologi Dalam Digital Entrepreneurship di SMK Negeri 2 Tondano - Rondonuwu, Yudith; Giroth, Lady Jane Grace; Mewengkang, Alfrina; Pangalila, Fiska Chintya Ezra; Taroreh, Tannezia (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
Digital entrepreneurship has changed the business world. New, creative, and effective models have emerged. We look at how digital technologies, including digital platforms, the internet, and mobile devices, affect the growth and success of small and medium-sized enterprises (SMEs) in digital entrepreneurship. Using tools such as e-commerce, social media, and data analytics, companies can optimize their business operations, access international markets, and improve customer engagement. Cloud computing, artificial intelligence, and blockchain are some of the technologies that are critical to digital entrepreneurship. In addition, they face challenges such as data security and the need for digital skills. Results show that while constant change is necessary, the right application of technology can bring innovation, greater market opportunities, and better competitiveness.